Survei Kondisi Fisik Atlet Futsal Usia 9–12 Tahun di Madrasah Ibtidaiyah Pesantren Nurul Islam - Mohammad Rizal; Moh. Hanafi; Mulyono Mulyono (Kampus Akademik Publiser, 2026)
The purpose of this study is to determine the Physical Condition Ability Level of Futsal Athletes at Madrasah Ibtidaiyah Pesantren Nurul Islam in 2026. This research is quantitative research using a descriptive method. The subjects of this study are Futsal athletes at Madrasah Ibtidaiyah Pesantren Nurul Islam in 2026, totaling 20 athletes. The data collection technique used a physical condition test instrument consisting of 5 test items, namely: sit-up test, vertical jump, 30m sprint, T test, and sit and reach. The data analysis technique used in this study is descriptive statistical analysis with percentages. Based on the results of the study using the physical condition test instrument on the level of physical condition ability of Futsal students at Madrasah Ibtidaiyah Pesantren Nurul Islam in 2026, the percentages are as follows: there are 0 athletes (0%) in the “Very Good” category, 4 athletes (20%) in the “Good” category, 14 athletes (70%) in the “Average” category, 2 athletes (10%) in the